ANALISIS POLA ASUH ORANG TUA PADA KESEHATAN MENTAL REMAJA DI DESA RENAH KURUNG - Putri Rachmawati Wahyuni Asyri Ep; Viktorwot; Ali Shabet; Ifnaldi Nurmal; Edi Wahyudi (STKIP Subang, 2026)
Parents play a role in shaping adolescent mental health through parenting styles applied in daily life. Adolescence is a developmental phase that is vulnerable to various mental health problems and therefore requires optimal family support. This study aims to analyze parental parenting styles on adolescent mental health in Renah Kurung Village, identify the types of parenting styles applied, analyze their impact on adolescent mental health, and examine the factors that influence the implementation of these parenting styles. The study used a descriptive qualitative method involving 9 informants consisting of 3 adolescents, 4 parents, and 2 additional informants. The results showed that parenting styles applied by parents in Renah Kurung Village consisted of authoritarian parenting, mixed permissive-authoritarian parenting, and mixed democratic parenting dominated by authoritarian characteristics. Authoritarian parenting was found to be the most dominant form of parenting, especially for adolescent girls. The impact of parenting styles on adolescent mental health includes a tendency to become withdrawn, the emergence of passive-aggressive behavior, fear in expressing opinions and making decisions, feelings of stress, and a tendency to self-harm. Factors influencing parenting styles include economic factors, the child's gender, the social environment, the parent's childhood parenting experiences, and the parent's personality. This research shows that authoritarian parenting styles have the potential to negatively impact adolescent mental health.